2008
DOI: 10.1149/1.2820626
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered Indium-Tin-Oxide on p-GaN

Abstract: To study plasma-induced damages, we directly sputtered indium-tin-oxide ͑ITO͒ films onto p-GaN and systematically studied the effects of sputter power on the electrical properties of ITO/p-GaN. It was found that plasma bombardment during sputtering will induce nitrogen vacancies and compensate acceptor concentration in p-GaN or even convert p-GaN into n-GaN. It was also found that annealing the samples at 600 and 700°C will generate more nitrogen vacancies and enhance rectifying behavior. Furthermore, it was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…12 The discrepancy may be partly attributed to surface damage induced by plasma during the initial stage of sputtering deposition. 21 As also seen in Fig. 4, when the annealing temperature is increased to 800°C, a sharp increase in contact resistance is observed, especially for the Ni/ITO contact.…”
Section: Resultssupporting
confidence: 69%
“…12 The discrepancy may be partly attributed to surface damage induced by plasma during the initial stage of sputtering deposition. 21 As also seen in Fig. 4, when the annealing temperature is increased to 800°C, a sharp increase in contact resistance is observed, especially for the Ni/ITO contact.…”
Section: Resultssupporting
confidence: 69%
“…The g m-max for samples C, D and E were 132, 147 and 160 mS/mm, respectively. The highest g m-max of sample E indicated that the mobility is highest among the three samples, which is possibly because, for sample E, the low electron density and no sputtering-induced surface damage [32] suppress the electron scattering. curve.…”
Section: Resultsmentioning
confidence: 93%
“…curve. I G-off on the order of 10 mA/mm for sample A is more than one order of magnitude larger than that of sample B (10 −1 mA/mm), which is possibly due to the higher sputter-induced shallow donor-like N vacancies [32][33][34] and much more N equ for oxide deposited at lower substrate temperature. I G-off for sample C is in the order of 10 −2 mA/mm, which is also one order of magnitude larger than that for sample D (10 −3 mA/mm).…”
Section: Resultsmentioning
confidence: 99%
“…9892 98920Y-7 and ITO, making it difficult for the contact to survive the high current densities required in VCSELs (typically tens of kA/cm 2 ). ITO deposition, usually done by sputtering to achieve high quality 115 , can easily lead to plasma damage of the p-GaN 116,117 , preventing a low-resistive contact to be formed. Remote plasma deposition or physical vapor deposition such as electron beam evaporation can be used to avoid plasma damage of the p-GaN.…”
mentioning
confidence: 99%